Revamping Pentecostal Evangelism: Appropriating Walter J. Hollenweger's Radical Proposal - Richie, Tony (International review of mission, 2007)
As the Christian Church endeavours to be faithful to its evangelistic mission, increasingly intense problems arise in international contexts of cultural diversity and religious plurality. Pentecostal, noted for “aggressive evangelism”, are frequently at the forefront of such negative encounters. Walter J. Hollenweger offers Pentecostals a complementary paradigm of “dialogical evangelism” that is sensitive to this situation without stilling the voice of evangelism. The present project overviews Hollenweger's “radical proposal” and traditional Pentecostal evangelism and its current trends before assessing their compatibility or contradictoriness and exploring possible appropriation.